Beyond the blueprint: (De)constructing mentorship for mid-career academics - Matisonn, Heidi; Hlengwa, Amanda (Critical Studies in Teaching and Learning, 2025)
While mentorship has existed ever since Odysseus set sail for Troy, in recent decades, there has been an explosion of interest in the concept. Although there is no consensus on what the ‘best’ model of mentorship is, there is acceptance that mentoring plays a crucial role in the success of academic careers. In what follows, we use collaborative autoethnography to present our contrasting experiences to explore the connection between mentoring and the progression of an academic through the various stages of their career. We employ the analogy of building a house and making a home to argue that while early career academics can benefit from mentorship that addresses the basic elements of an academic career, mid-career academics require more specialised interventions - some of which go beyond mentoring - that are tailored to the individual needs and personal plans for shaping their careers.